2016
DOI: 10.1371/journal.pone.0146708
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin Beta-4 Suppresses Osteoclastic Differentiation and Inflammatory Responses in Human Periodontal Ligament Cells

Abstract: BackgroundRecent reports suggest that thymosin beta-4 (Tβ4) is a key regulator for wound healing and anti-inflammation. However, the role of Tβ4 in osteoclast differentiation remains unclear.PurposeThe purpose of this study was to evaluate Tβ4 expression in H2O2-stimulated human periodontal ligament cells (PDLCs), the effects of Tβ4 activation on inflammatory response in PDLCs and osteoclastic differentiation in mouse bone marrow-derived macrophages (BMMs), and identify the underlying mechanism.MethodsReverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The beta-thymosin family, primarily including thymosin beta 4 (TMSB4), TMSB10 and TMSB15, function as actin-sequestering proteins to inhibit actin polymerization and disrupt the formation of F-actin [ 5 ]. Furthermore, beta-thymosins exhibit diverse physiological functions beyond actin sequestration, including tissue development and regeneration, anti-inflammatory effects, and induction of insulin secretion [ 6 10 ]. Recent studies have focused on the biological roles of beta-thymosins in the progression and metastasis of various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The beta-thymosin family, primarily including thymosin beta 4 (TMSB4), TMSB10 and TMSB15, function as actin-sequestering proteins to inhibit actin polymerization and disrupt the formation of F-actin [ 5 ]. Furthermore, beta-thymosins exhibit diverse physiological functions beyond actin sequestration, including tissue development and regeneration, anti-inflammatory effects, and induction of insulin secretion [ 6 10 ]. Recent studies have focused on the biological roles of beta-thymosins in the progression and metastasis of various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a plausible role for Tβ4 in bone degradation by stimulating MMP expression would be inconsistent with a beneficial role in bone metabolism, which Tβ4 has been reported to play (49) by suppressing osteoclastic differentiation in RANKL-stimulated mouse bone-marrow-derived macrophages through the inhibition of osteoclast-specific gene expression, as well as p38, ERK, and JNK phosphorylation and NF-κB activation (50). Furthermore, Tβ4 promotes differentiation and mineralization of MC3T3-E1 cells, which are an osteoblast precursor derived from mouse calvaria (51).…”
Section: Thymosin β4 and Rheumatoid Arthritismentioning
confidence: 99%
“…It was demonstrated that wnt5a mRNA is upregulated in the gingiva of patients with periodontitis (Nanbara et al., ) and a genome‐wide association study found suggestive evidence of association for the wnt5a gene and severe periodontitis (Divaris et al., ). The evolutionary conserved sFRP5 and wnt5a system has increasingly gained attention in the research field of periodontitis over the last years (Divaris et al., ; Hu et al., ; Lee et al., ; Nanbara et al., ; Xu et al., ; Yu et al., ; Zhou, Dorfer, Chen, & Fawzy El‐Sayed, ). Recently, a reciprocal relationship between sFRP5 and wnt5a expression in periodontal health and disease , as well as that sFRP5 could block experimental periodontal inflammation in vivo , was demonstrated (Maekawa et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The evolutionary conserved sFRP5 and wnt5a system has increasingly gained attention in the research field of periodontitis over the last years (Divaris et al, 2013;Hu et al, 2016;Lee et al, 2016;Nanbara et al, 2012;Xu et al, 2015;Yu et al, 2015;Zhou, Dorfer, Chen, & Fawzy El-Sayed, 2017). Recently, a reciprocal relationship between sFRP5 and wnt5a expression in periodontal health and disease, as well as that sFRP5 could block experimental periodontal inflammation in vivo, was demonstrated (Maekawa et al, 2017).…”
mentioning
confidence: 99%